2010
DOI: 10.1089/rej.2009.0960
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Repair in the Parkinsonian Nonhuman Primate Brain

Abstract: Parkinson disease (PD) is a neurodegenerative disorder that provides a useful model for testing cell replacement strategies to rejuvenate the affected dopaminergic neural systems, which have been destroyed by aging and the disease. We first showed that grafts of fetal dopaminergic neurons can reverse parkinsonian motor deficits induced by the toxin, 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), validating the feasibility of cellular repair in a primate nervous system. Subsequent clinical trials in Parki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Cell therapy is one potential future application of stem cells, especially of iPSCs, given the possibility of autologous transplantation (Brundin et al, 2010; Redmond et al, 2010; Deleidi et al, 2011). Although teratomas are rejected by syngenic mice, stem cell therapy will unlikely employ iPSCs themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Cell therapy is one potential future application of stem cells, especially of iPSCs, given the possibility of autologous transplantation (Brundin et al, 2010; Redmond et al, 2010; Deleidi et al, 2011). Although teratomas are rejected by syngenic mice, stem cell therapy will unlikely employ iPSCs themselves.…”
Section: Discussionmentioning
confidence: 99%
“…A significant advantage of the use of large, long-lived animals is the ability to have a longer observation time for possible side effects as well as therapeutic benefits. The use of non-human primates also permitted the evaluation of the potential for reconstruction of the full dopaminergic pathway by co-grafting fetal tissue or growth factors into the striatum and substantia nigra at distances similar to those in the human brain [40]. Despite these advances in animal models, human trials so far have shown very modest and variable improvement, indicating that further optimization of techniques is required to improve efficacy before clinical use.…”
Section: Testing Stem Cell Therapies For Specific Disease Conditions mentioning
confidence: 99%
“…That there have been some successful outcomes provides proof of concept that replacing lost neural cells through neural grafting or implantation can be a viable treatment option. However, the large scale loss of grafted cells in the days following implantation is most likely the biggest contributor to their variable success (Barker et al, 1996; Meyer et al, 1998; Bjugstad et al, 2008; Yu et al, 2009; Redmond et al, 2010). To improve the outcomes of cell implantation into the central nervous system (CNS), there needs to be some method of protecting the neural grafts from the host response to the implant procedure and for guiding graft growth and integration.…”
Section: Introductionmentioning
confidence: 99%